Glycosmisines A and B: isolation of two new carbazole–indole-type dimeric alkaloids from Glycosmis pentaphylla and an evaluation of their antiproliferative activities1. Issue 24 (28th June 2015) - Chen, Yu; Tang, Chu; Wu, Yi; Mo, Shasha; Wang, Sha; Yang, Guangzhong; Mei, Zhinan
<x xml:space="preserve">Abstract</x> Two unique carbazole–indole-type dimeric alkaloids, glycosmisines A (1) and B (2), have been isolated from the stems of Glycosmis pentaphylla and their structures are elucidated by 1D and 2D NMR analyses).